2008
DOI: 10.1007/s12274-008-8050-3
|View full text |Cite
|
Sign up to set email alerts
|

A lamellar ceria structure with encapsulated platinum nanoparticles

Abstract: A novel lamellar feather-like CeO 2 structure has been fabricated by using a triblock copolymer as the structuredirecting agent. This material was characterized in detail by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and BET surface area measurements. Compared with conventional spherical shaped ceria prepared by ammonia gelation, the ceria feathers have superior ability to support nanosized platinum particles due to their special structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Pt was attached using a sonication method but the activity of the catalyst was lower compared to other previously reported catalysts. 26 Lin et al reported a platinum decorated ceria supported catalyst synthesized by the e-beam evaporation method and found that the catalyst with rods as the support is more active for CO oxidation than the catalyst with octahedra as the support. 21 Thus, it is necessary to understand the role of different planes and oxygen vacancies in CO oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pt was attached using a sonication method but the activity of the catalyst was lower compared to other previously reported catalysts. 26 Lin et al reported a platinum decorated ceria supported catalyst synthesized by the e-beam evaporation method and found that the catalyst with rods as the support is more active for CO oxidation than the catalyst with octahedra as the support. 21 Thus, it is necessary to understand the role of different planes and oxygen vacancies in CO oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…CO oxidation on this catalyst showed 22% conversion at 225 °C, whereas 100% conversion was obtained at 330 °C. 26 Lin et al reported an electron beam evaporation method to decorate Pt nanoclusters on CeO 2 nanorods and nano-octahedra. They observed that Pt decorated nanorods were 17 times more active than the Pt decorated nano-octahedra catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…For the construction of CeO 2 mesoporous materials, the most common approach is the use of hard or soft sacrificial templates. For example, Corma and co-workers have synthesized mesostructured CeO 2 materials using CeO 2 nanoparticles as starting materials and a EO 20 PO 70 EO 20 triblock copolymer as the soft template . Stucky and co-workers used MCl n as the metal source and poly(ethylene oxide)-based triblock copolymers as soft templates in an ethanolic solution to synthesize mesoporous metal oxides. , CeO 2 mesoporous materials have been synthesized by using SBA-15 and KIT-6 as sacrificial templates . However, there are limited reports for the direct and template-free synthesis of CeO 2 mesostructures, especially mesostructures with narrow pore distributions, rigid frameworks, and well-defined morphologies until now.…”
mentioning
confidence: 99%
“…The rod-like structure belongs to neodymium, and the feather-like structure belongs to cerium, in addition to the elongated particles of hydroxyapatite; this was obvious from the FESEM image with a magnification of 100.00 KX and resolution of 100 nm. From these images, it is evident that the final structure of hydroxyapatite depends on the conditions of preparation and elements added during the synthesis process [ 38 – 40 ].…”
Section: Resultsmentioning
confidence: 99%